The Importance of Agrotechnical Measures in the Cultivation of Grape (Vitis vinifera L.) - Jolbekov, Ibrohim; Abdug‘aniyeva , Feruza (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article examines the effects of agrotechnical measures—particularly the application of organic and mineral fertilizers—on yield and quality indicators in the cultivation of grape (Vitis vinifera L.) varieties, including application rates, timing, and efficiency. It also provides information on the biological characteristics of grapevines, their root system, propagation methods, classification of grape varieties, and soil management practices in vineyards. The research findings offer practical recommendations for farms, viticulture clusters, and scientific institutions to ensure sustainable, environmentally friendly, and highly profitable grape production.